2005
DOI: 10.1161/01.atv.0000168909.44877.a7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Cardiovascular Disease Risk in Familial Hypercholesterolemia

Abstract: Objective-To investigate the contribution of polymorphisms in multiple candidate genes to cardiovascular disease (CVD) risk in a large cohort of patients with heterozygous familial hypercholesterolemia (FH). (FH) is a common hereditary disease, characterized by elevated levels of plasma low-density lipoprotein cholesterol (LDL-C) and premature cardiovascular disease (CVD). 1 Characteristically, the mean age of onset of CVD is between 40 and 45 years in male FH patients and in female FH patients 10 years lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 30 publications
(23 reference statements)
0
37
0
Order By: Relevance
“…Thus, in order to identify most mutation carriers, even patients with only possible FH must be genotyped as recently suggested by Damgaard et al [19]: They tested the ability of three clinical diagnosis tools to predict mutation status in FH individuals but did only find a tenuous relationship of genotype to phenotype. These findings warrant continued investigation to reveal which factors to include to optimize the mutation screening procedure as in a recent work by Jansen et al, who screened for a wide variety of gene mutations [20].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, in order to identify most mutation carriers, even patients with only possible FH must be genotyped as recently suggested by Damgaard et al [19]: They tested the ability of three clinical diagnosis tools to predict mutation status in FH individuals but did only find a tenuous relationship of genotype to phenotype. These findings warrant continued investigation to reveal which factors to include to optimize the mutation screening procedure as in a recent work by Jansen et al, who screened for a wide variety of gene mutations [20].…”
Section: Discussionmentioning
confidence: 90%
“…Other loci causing clinical FH has been reported [12,22] and the mutation prevalence at these loci will be interesting, as recent studies seems to imply an explanation for the discordance observed [23]. Furthermore, additional mutations in the gene coding for lipoprotein lipase (LPL) has been reported capable of deteriorating the FH phenotype [24], and lately, mutation in the prothrombin gene has been suggested [20]. Of note, the Bonferroni test and the AUC plot ( Fig.…”
Section: Discussionmentioning
confidence: 91%
“…14 However, in that publication, the threshold to reach statistical significance was rather lenient. In this paper, a P-value o0.001 was considered statistically significant; however, applying the Bonferroni correction, which is common practice nowadays would suggest a P-value o0.00076.…”
Section: Discussionmentioning
confidence: 93%
“…An additive genetic model was applied in the Cox model and classical cardiovascular risks were used as covariates. 21 We corrected for factors that had previously been shown to be associated with CAD risk in this population: age, gender, smoking, type 2 diabetes, hypertension and body mass index (BMI). Analyses were performed for the loci previously reported to be associated with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…10 Three polymorphisms had only wild-type alleles in our population and were therefore excluded from the present analyses. All patients gave informed consent and the ethics institutional review board of each participating hospital approved the protocol.…”
Section: Study Populationmentioning
confidence: 99%